On the interactions between mesenchymal stem cells and regulatory T cells for immunomodulation in transplantation - Engela, Anja U.; Baan, Carla C.; Dor, Frank J.; Weimar, Willem; Hoogduijn, Martin J. (Frontiers in Immunology, 2012)
Experimental studies have established the use of mesenchymal stem cells (MSC) as a candidate immunosuppressive therapy. MSC exert their immunomodulatory function through the inhibition of CD4+ and CD8+ T cell proliferation. It is unknown whether MSC impair the immunosuppressive function of regulatory T cells (Treg). In vitro and in vivo studies suggest that MSC mediate their immunomodulatory effects through the induction of Treg. In this review we will focus on the interactions between MSC and Treg, and evaluate the consequences of these cellular interplays for prospective MSC immunotherapy in organ transplantation.